2015
DOI: 10.1007/s13277-015-3863-7
|View full text |Cite|
|
Sign up to set email alerts
|

UBE2S is associated with malignant characteristics of breast cancer cells

Abstract: Ubiquitination is essential for various biological processes, such as signal transduction, intracellular trafficking, and protein degradation. Accumulating evidence has demonstrated that ubiquitination plays a crucial role in cancer development. In this report, we examine the expression and function of ubiquitin-conjugating enzyme E2S (UBE2S) in breast cancer. Immunohistochemical analysis revealed that UBE2S is highly expressed in breast cancer. The depletion of UBE2S by siRNA induced disruption of the actin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…KNTC1 may have an essential role in mediating cell viability and apoptosis in human ESCC cells and may serve as a novel therapeutic target for esophageal squamous cell carcinoma [26]. Ubiquitin-conjugating enzyme E2S (UBE2S) knockdown suppressed the malignant characteristics of breast cancer cells, such as migration, invasion, and anchorage-independent growth [27]. In this study, we found that they were associated with overall survival in patients with ccRCC.…”
Section: Discussionmentioning
confidence: 70%
“…KNTC1 may have an essential role in mediating cell viability and apoptosis in human ESCC cells and may serve as a novel therapeutic target for esophageal squamous cell carcinoma [26]. Ubiquitin-conjugating enzyme E2S (UBE2S) knockdown suppressed the malignant characteristics of breast cancer cells, such as migration, invasion, and anchorage-independent growth [27]. In this study, we found that they were associated with overall survival in patients with ccRCC.…”
Section: Discussionmentioning
confidence: 70%
“…Although there are few studies on the roles of UBE2S and UBE2V2 in OC, both genes are involved in the occurrence and progression of other tumors. UBE2S was reported to be aberrantly expressed in some gynecological tumors, including breast, cervical, and endometrial cancer, and its knockdown inhibits the proliferation of cancer cells and promotes apoptosis [45][46][47]. UBE2V2 overexpression seems to be involved in the pathogenesis of gastric cancer, and is signi cantly associated with poor prognosis in ERpositive/HER2-negative breast cancer [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few studies on the roles of UBE2S and UBE2V2 in OC, both genes are involved in the occurrence and progression of other tumors. UBE2S was reported to be aberrantly expressed in some gynecological tumors, including breast, cervical, and endometrial cancer, and its knockdown inhibits the proliferation of cancer cells and promotes apoptosis [45][46][47]. UBE2V2 overexpression seems to be involved in the pathogenesis of gastric cancer, and is signi cantly associated with poor prognosis in ER-positive/HER2negative breast cancer [48,49].…”
Section: Discussionmentioning
confidence: 99%